Check-in Handling by Receptionist to Improve Service Quality - Ni Kadek Cita Sari; Ni Putu Wiwiek Ary Susyarini; I Ketut Suarja; Made Sudiarta (International Journal of Glocal Tourism, 2020)
Purpose: This research is done to find out the implementation of check in handling by receptionist in improving the quality of service at a 5 star hotel located in Ubud tourist area, Gianyar, Bali, Indonesia. Research methods: Data collection methods used are observation, interviews, questionnaires, and literature study. The analysis technique used in this research is qualitative descriptive using a 4 level likert scale. Findings: The overall implementation of check in handling has been implemented to the maximum, but there are some standard operating procedures (SOP) that are lacking in its application. Implication: It takes effort from the receptionist to be able to implement maximum check in SOP in order to improve the quality of hotel services.